2020
DOI: 10.1520/jte20180550
|View full text |Cite
|
Sign up to set email alerts
|

On Designing Distribution-Free Homogeneously Weighted Moving Average Control Charts

Abstract: There are many practical situations in which the underlying process distribution is either completely unknown or partially known but deviates from normality. In such cases, the performance of the traditional parametric control charts deteriorates, and nonparametric control charts are considered as a robust alternative for monitoring the process. In this article, two new nonparametric homogeneously weighted moving average (NPHWMA) control charts are proposed for monitoring the deviations in process location fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…More recently, Abbas (2018) developed a new memory-type scheme that allocates a specific weight to the current sample and the remaining weight is distributed equally among the previous samples; this scheme is known as the homogeneously weighted moving average (HWMA) monitoring scheme. The HWMA scheme is by its nature a memory-type scheme used to effectively monitor small-to-moderate shifts (see for example the following articles on the HWMA-type monitoring schemes: Abbas (2018), Abbas et al (2020), Abid et al (2020a, b), Adegoke et al (2019a, b), Adeoti and Koleoso (2020), Dawod et al (2020), Nawaz and Han (2020), Raza et al (2020). Nawaz and Han (2020) studied the performance of the HWMA scheme using structured sampling techniques, that is, ranked set sampling (RSS), extreme RSS, median RSS and neoteric RSS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Abbas (2018) developed a new memory-type scheme that allocates a specific weight to the current sample and the remaining weight is distributed equally among the previous samples; this scheme is known as the homogeneously weighted moving average (HWMA) monitoring scheme. The HWMA scheme is by its nature a memory-type scheme used to effectively monitor small-to-moderate shifts (see for example the following articles on the HWMA-type monitoring schemes: Abbas (2018), Abbas et al (2020), Abid et al (2020a, b), Adegoke et al (2019a, b), Adeoti and Koleoso (2020), Dawod et al (2020), Nawaz and Han (2020), Raza et al (2020). Nawaz and Han (2020) studied the performance of the HWMA scheme using structured sampling techniques, that is, ranked set sampling (RSS), extreme RSS, median RSS and neoteric RSS.…”
Section: Introductionmentioning
confidence: 99%
“…Dawod et al (2020) proposed a bivariate HWMA scheme based on linear profiles to monitor the intercept, slope and variance parameters using the Bayesian estimation model and showed that it outperforms its competitors. Finally, Raza et al (2020) proposed a distribution-free HWMA scheme based on the sign and signed-rank statistics to monitor skewed and symmetric distributions observations. The key difference between the HWMA scheme proposed in this paper and the abovementioned HWMA schemes is that it is not assumed that the observations have perfect or exact measurements.…”
Section: Introductionmentioning
confidence: 99%
“…For the multivariate scenario, [40] and [41] studied the performance of the HWMA scheme in detecting shifts in the process mean vector in Cases K and U, respectively. For nonparametric schemes, [42] studied the performance of the HWMA scheme based on the sign and signed-rank statistics to monitor symmetric and skewed distributions which are applicable in the Case K scenario.…”
Section: Introductionmentioning
confidence: 99%
“…The synthetic version of the EWMA sign control chart was proposed by Haq [18] by integrating the existing EWMA sign control chart with the conforming run length. Recently, Raza et al [19] proposed the nonparametric homogeneously weighted moving average control charts based on sign and signed-rank statistics.…”
Section: Introductionmentioning
confidence: 99%